Bacterial Diversity Associated With the Rhizosphere and Endosphere of Two Halophytes: Glaux maritima and Salicornia europaea - Yamamoto, Kosuke; Shiwa, Yuh; Ishige, Taichiro; Sakamoto, Hikaru; Tanaka, Keisuke; Uchino, Masataka; Tanaka, Naoto; Oguri, Suguru; Saitoh, Hiromasa; Tsushima, Seiya (Frontiers in Microbiology, 2018)
Root-associated microbial communities are very important in the adaptation of halophytes to coastal environments. However, little has been reported on microbial community structures related to halophytes, or on comparisons of their compositions among halophytic plant species. Here, we studied the diversity and community structure of both rhizosphere and root endosphere bacteria in two halophytic plants: Glaux maritima and Salicornia europaea. We sampled the rhizosphere, the root endosphere, and bulk control soil samples, and performed bacterial 16S rRNA sequencing using the Illumina MiSeq platform to characterize the bacterial community diversities in the rhizosphere and root endosphere of both halophytes. Among the G. maritima samples, the richness and diversity of bacteria in the rhizosphere were higher than those in the root endosphere but were lower than those of the bulk soil. In contrast for S. europaea, the bulk soil, the rhizosphere, and the root endosphere all had similar bacterial richness and diversity. The number of unique operational taxonomic units within the root endosphere, the rhizosphere, and the bulk soil were 181, 366, and 924 in G. maritima and 126, 416, and 596 in S. europaea, respectively, implying habitat-specific patterns for each halophyte. In total, 35 phyla and 566 genera were identified. The dominant phyla across all samples were Proteobacteria and Bacteroidetes. Actinobacteria was extremely abundant in the root endosphere from G. maritima. Beneficial bacterial genera were enriched in the root endosphere and rhizosphere in both halophytes. Rhizobium, Actinoplanes, and Marinomonas were highly abundant in G. maritima, whereas Sulfurimonas and Coleofasciculus were highly abundant in S. europaea. A principal coordinate analysis demonstrated significant differences in the microbiota composition associated with the plant species and type of sample. These results strongly indicate that there are clear differences in bacterial community structure and diversity between G. maritima and S. europaea. This is the first report to characterize the root microbiome of G. maritima, and to compare the diversity and community structure of rhizosphere and root endosphere bacteria between G. maritima and S. europaea.